中小學教師老化教育培訓方案實施成效之實驗研究 Effects of Aging Education Training on Elementary and Secondary Teachers Toward Aging - 黃錦山 Chin-Shan Huang (National Taiwan Normal University, 2018)
近年來高齡人口數逐年增多，但現代老人的地位卻因工商業社會的發展而逐年下降，致使年齡歧視現象充斥於社會之中。如何能夠消弭年齡歧視的蔓延，有賴於中小學教師具有老化教育的相關培訓。因此，本研究旨於規劃 18 小時的「教師老化教育培訓方案」是否能有效地改善中小學教師的老化知識、態度與教學行為意向？本研究採取「不等組前後測設計」，有效樣本實驗組 33 人、控制組 51 人。主要研究發現有：一、實驗組教師在接受「老化教育培訓方案」後，其老化知識、態度與教學行為意向上的得分，顯著較其培訓前佳；二、控制組教師在未接受「老化教育培訓方案」的情況下，其老化知識、態度與教學行為意向上的前後測得分，無顯著差異；三、實驗組教師在接受「老化教育培訓方案」後，其老化知識、態度與教學行為意向上的得分，顯著較控制組教師佳。 The aging population is gradually increasing because people are living longer. Older people are often portrayed as insignificant, unhealthy, sad, and dependent in contemporary cultures and values. Therefore, it is pertinent to improve the knowledge, attitudes, and behavioral intentions toward aging and older people held by elementary and secondary teachers. The researcher designed an 18-hour Aging Education Training (AET) program to test whether it influenced the knowledge, attitudes, and behavioral intentions of the participants. Overall, 33 teachers were in an experimental group and 51 teachers were in a control group. The results revealed that the teachers who joined the AET program had improved knowledge, attitudes, and behavioral intentions toward aging people after the training program. Conversely, there was no significant difference in the knowledge, attitudes, and teaching behavior toward aging people in the teachers who did not join the AET program. Overall, the teachers who joined the AET program had significantly greater knowledge, attitudes, and teaching behavior toward aging people compared with the teachers who did not join the AET program.